Geographic Variation of Bufo spinulosus in Chile - Cei, José Miguel Alfredo María (1960)
Analysis of geographic variation shows that populations of Bufo spinulosus Wiegmann are differentiated in Chile. Four recognizable, though broadly intergrading, population groups are indicated, corresponding to: (1) the northern mountainous arid environment of the Pune de Atacama plateau; (2) the isolated valleys and streams of the desert area of Atacama; (3) the central area between Coquimbo and Angol; and (4) the southern, humid Valdivian Forest. Polymorphism was observed in some characters and clinal tendencies in others.